The Magellan M2FS Spectroscopic Survey of High-redshift Galaxies: The Brightest Lyman-break Galaxies at z ∼ 6 - Shuqi Fu; Linhua Jiang; Yuanhang Ning; Weiyang Liu; Zhiwei Pan (The Astrophysical Journal, 2024)
We present a study of a sample of 45 spectroscopically confirmed, UV luminous galaxies at z ∼ 6. They were selected as bright Lyman-break galaxies (LBGs) using deep multiband optical images in more than 2 deg ^2 of the sky, and subsequently identified via their strong Ly α emission. The majority of these LBGs span an absolute UV magnitude range from −22.0 to −20.5 mag with Ly α equivalent width (EW) between ∼10 and ∼200 Å, representing the most luminous galaxies at z ∼ 6 in terms of both UV continuum emission and Ly α line emission. We model the spectral energy distributions of 10 LBGs that have deep infrared observations from Hubble Space Telescope, JWST, and/or Spitzer, and find that they have a wide range of stellar masses and ages. They also have high star formation rates ranging from a few tens to a few hundreds of solar mass per year. Five of the LBGs have JWST or HST images, and four of them show compact morphology in these images, including one that is roughly consistent with a point source, suggesting that UV luminous galaxies at this redshift are generally compact. The fraction of our photometrically selected LBGs with strong Ly α emission (EW > 25 Å) is about 0.2, which is consistent with previous results and supports a moderate evolution of the intergalactic medium opacity at the end of cosmic reionization. Using deep X-ray images, we do not find evidence of strong active galactic nucleus (AGN) activity in these galaxies, but our constraint is loose, and we are not able to rule out the possibility of any weak AGN activity.